Pengaruh Utang Luar Negeri Terhadap Pertumbuhan Ekonomi Indonesia (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
The purpose of this study is to determine the existence of influence, relationship, and behavior of foreign debt on economic growth. The Vector Error Correction Model method is used on time series data to answer this goal. The results showed that foreign debt had a significant negative influence on economic growth during the period. Similarly, inflation and exchange rates are chosen to have significant negative influences. Meanwhile, exports have a significant positive influence on growth. Savings and road length as infrastructure proxies also have a negative but not significant influence on economic growth. Meanwhile, there is a long-term relationship or cointegration between economic growth, external debt, savings ratio, export ratio, inflation, road length, and exchange rate. The external debt response to shocks to economic growth was negative. That is, an increase in economic growth will bring foreign debt to decrease. In the first year, the external debt response to the shock of an increase in GDP growth of 1 standard deviation was responded negatively at -23.63 and began to reach equilibrium in the 5th period. This negative influence shows that Indonesia's foreign debt has been a burden on economic growth